Uji Kekerasan Pada Pegas Daun Mobil Pick-up. Suhu Pemanasan 8000c Di Quenching Air Laut - Erizal Erizal (MAJALAH TEKNIK SIMES, 2017)
Heat treatment process on low carbon steel is very useful for getting qualified low carbon steel that has physical properties such as electrical conductivity, microstructure, density and better mechanical properties especially in term of hardness, elasticity of steel caracter.This process is carried out at 800 Â°C for 30 minutes, then cooled with sea water as cooling medium. The result showed that the hardness value of speciment without treatment is 38,571 HRC, whereas hardness value of speciment with treatment is 61 HRC. This research can be concluded that quenching process can increase the hardness value